A Novel Dietary Supplement Containing Multiple Phytochemicals and Vitamins Elevates Hepatorenal and Cardiac Antioxidant Enzymes in the Absence of Significant Serum Chemistry and Genomic Changes. Issue 2 (2010) - Bulku, Elida; Zinkovsky, Daniel; Patel, Payal; Javia, Vishal; Lahoti, Tejas; Khodos, Inna; Stohs, Sidney J.; Ray, Sidhartha D.
Abstract : A novel dietary supplement composed of three well-known phytochemicals, namely, Salvia officinalis (sage) extract, Camellia sinensis (oolong tea) extract, and Paullinia cupana (guarana) extract, and two prominent vitamins (thiamine and niacin) was designed to provide nutritional support by enhancing metabolism and maintaining healthy weight and energy. The present study evaluated the safety of this dietary supplement (STG; S, sage; T, tea; G, guarana) and assessed changes in target organ antioxidant enzymes (liver, kidneys and heart), serum chemistry profiles and organ histopathology in Fisher 344 rats. Adult male and female Fisher 344 rats were fed control (no STG) or STG containing (1X and 7X, 1X = daily human dose) diets and sacrificed after 2 and 4 months. Serum chemistry analysis and histopathological examination of three vital target organs disclosed no adverse influence on protein, lipid and carbohydrate profiles, genomic integrity of the liver and/or the tissue architecture. However, analysis of the most important antioxidant components in the liver, kidney and heart homogenates revealed a dramatic increase in total glutathione concentrations, glutathione peroxidase and superoxide dismutase enzyme activities. Concomitantly, oxidative stress levels (malondialdehyde accumulation) in these three organs were less than control. Organ specific serum markers (ALT/AST for the liver; CPK/AST/LDH for the heart; BUN/creatinine for kidneys) and the genomic integrity disclosed no STG-induced alteration. Some of the serum components (lipid and protein) showed insignificant changes. Overall, STG-exposed rats were more active, and the results suggest that STG exposure produces normal serum chemistry coupled with elevated antioxidant capacity in rats fed up to seven times the normal human dose and does not adversely influence any of the vital target organs. Additionally, this study reiterates the potential benefits of exposure to a pharmacologically relevant combination of phytochemicals compared to a single phytochemical entity.